Impact of forty-seven years of long-term fertilization and liming on soil health, yield of soybean and wheat in an acidic Alfisol. Issue 4 (21st March 2022) - ., Vishwanath; Kumar, Sarvendra; Purakayastha, Tapan Jyoti; Datta, Siba Prasad; K.G., Rosin; Mahapatra, Prabhakar; Sinha, Subodh Kumar; Yadav, Surya Prakash
ABSTRACT: Fertilization with suitable amendment in acidic soil is crucial to achieve long-term high crop yield without deteriorating soil health in intensive cropping system. We studied the chemical and biological properties of soil, soybean, and wheat yield after 47 years of long-term fertilization in an acidic Alfisol. Treatments were: unfertilized (control); recommended N dose (N); recommended N and P (NP); recommended N, P and K (NPK); NPK + hand weeding (NPK + HW); NPK + 10 Mg ha −1 farmyard manure (NPK + FYM) and NPK + 0.40 Mg ha −1 lime (NPK + lime). Long-term application of NPK + FYM significantly enhanced the soil cation exchange capacity (CEC), organic carbon, available NPK and microbial functions compared to NPK. Application of NPK + lime increased soil pH, dehydrogenase activity (DHA) and bacterial population by 15.7%, 38.8% and 145% respectively, over NPK. Continuous inorganic-P fertilizer application leads to substantial build-up of available-P in soil. Fertilization of FYM/lime with NPK recorded higher crops yield compared to NPK. Soil DHA, bacterial population and CEC were most influencing factors governing grain yield. Overall, long-term application of NPK with FYM/lime improved soil health and crop yield, but rate of inorganic-P input should be curtailed in an Alfisol.